Evaluation of the prevalence of silicone oil droplets in the vitreous in patients treated with multiple intravitreal drug injections - E. V. Bobykin; I. A. Kulakova; O. V. Morozova; V. Ya. Krokhalev (Acta Biomedica Scientifica, 2021)
Background. At present, intraocular drops of silicone oil, which is a lubricant for disposable syringes used for intravitreal injections, are being actively studied. Among the undesirable effects of their presence are patient’s complaints of visual discomfort associated with floating opacities, as well as a potential connection with episodes of intraocular inflammation and increased intraocular pressure.The aim: to assess the prevalence of silicone oil droplets in the vitreous in patients treated with multiple intravitreal injections.Materials and methods. A single-center retrospective cohort study was carried out. Inclusion criterion: treatment with multiple (at least 5) intravitreal injections of drug solutions performed according to registered indications. The study group consisted of 86 eyes of 85 patients (56 women, 29 men; age – from 36 to 89 y.o., average – 71.7 y.o.), who received an average of 13.2 injections of solutions of various drugs.Results. Drops of silicone oil were detected by biomicroscopy in 57 eyes (66.28 %) and by ultrasonography in 76 (88.37 %). The coincidence of the results of applying the methods was recorded in 73.26 % of observations. Seven (8.1 %) patients had characteristic complaints. Four patients (4.7  %) had a history of aseptic vitreitis. The  hypothesis was  confirmed that the possibility of silicone oil droplets getting into the vitreous increases with the number of intravitreal injections. A similar relationship was established in relation to the possibility of the appearance of characteristic complaints in patients due to the presence of drops and episodes of aseptic vitreitis.Conclusion. The release of drops of silicone oil from syringes during intravitreal injections is an urgent problem that requires further study. In the Russian Federation, the situation is aggravated by the lack of prefilled syringes with drugs approved for administration into the eye cavity, as well as the lack of syringe models designed for use in ophthalmology.